Self-regulated reflection and design of work processes - Workers’ role between human resource and self-empowered individual - Oppl, Stefan (Momentum Quarterly, 2016)
The use of organizational and technical tools for workflow management and monitoring has been a continuous trend over the last decades. Such tools pursue a view on organizations, which largely ignores social and cognitive implications for the affected workers. Recent developments in socio-technical work support systems enable a more active role of workers in the design of work processes. Enabling workers to take this role, however, requires them to develop an understanding for the relevant forms of work representation, as well as to acquire skills for manipulating them and to be able to assess their implications for real world work processes. The present article introduces a design pattern for methods that should facilitate the development of these skills. It is based on collaborative alignment of mental models via conceptual modeling. The article introduces a method implementing the design pattern and reviews the results of an extensive evaluation in area of vocational training. The results indicate that the fundamental design goals have been achieved.